Haplótipos de diferentes SNPs no interior do gene FLI1 em indivíduos afetados e não-afetados pelo sarcoma de Ewing - Sawitzki, Fernanda Rosa (2012)
In this study the SNPs rs640098, rs491714, rs611307 into the FLI1 gene were genotyped in a sample of 201 subjects from southern Brazilian population, in 24 Ewing s sarcoma patients (geographically matched with control group) and 54 of their family members, including parents and siblings. We performed association studies comparing genotypic frequencies of rs640098, rs491714, rs611307 into the FLI1 gene, and all possible genotype combinations between Ewing s Sarcoma patients and control group. Of the three SNPs investigated individually, only one of them showed a significant result when compared to the control group; our non-combined analysis revealed a significantly higher presence of homozygote A-rs497714 among Ewing s Sarcoma patients (p=0.0065; Chi square Test). In all other tested clusters, we always noticed a higher rate of homozygote A-rs497714 among Ewing s Sarcoma patients independent of the other SNP-arrangements and/or haplotype combinations. In addition, we performed transmission disequilibrium tests comparing data from Ewing s Sarcoma patients and from their families (parents and siblings), but no statistically significant result was found. In conclusion, the present study provides evidence statistically founded that the AA-rs497714 FLI1 genotype can associated with Ewing's sarcoma. And that this polymorphism can be clinically useful as a potential genetic marker to the prognostic of risk to develop this cancer or to provide insights into FLI1 chromosome breakage context of tumorigenesis.